EKSISTENSI DALAM GLOBALISASI: PERAN WISATA KULINER DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI SANUR - Ida Bagus Ketut Soma Antara (Journal of Tourism and Interdiciplinary Studies, 2022)
Sanur is one of the tourism pioneers in Bali that has various tourist attractions, one of them is traditional Balinese culinary. There are various traditional Balinese culinary that have existed for decades in Sanur and need to be preserved. Culinary is not only an attraction for tourists, but also as a medium for developing sustainable tourism in Sanur. Based on this phenomenon, this research will discuss (1) the development of culinary tourism in Sanur, (2) the development strategy of culinary tourism in Sanur, and (3) the role of culinary tourism in the development of sustainable tourism in Sanur. This research uses qualitative methods, with in-depth interview. The theories used include gastronomic theory, the theory of five drivers of culinary tourism, and the theory of tourist experiences. The results of this study are (1) culinary tourism in Sanur is increasingly varied, as evidenced by the increasing number of restaurants that serves Balinese specialties; (2) the restaurant’s owners need to be more concern about hygiene and sanitation, hospitality, marketing strategy; (3) Culinary tourism is able to have a good impact in terms of the local economy, social, and culture.